Regional growth strategies: fiscal versus institutional governmental policies - Ingrid Ott; Susanne Soretz (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2006)
This paper analyzes the growth impact of fiscal and institutional governmental policies in a regional context. The government provides a productive input that is complementary to private capital. Institutional policies include the decision about the type of public input as well as on the size of the region as determined by the number of firms. Fiscal policies decide on the extent of the public input. Private capital accumulation incurs adjustment costs that depend upon the ratio between private and public investment. After deriving the decentralized equilibrium, fiscal and institutional policies as well as their interdependencies and welfare implications are discussed. Due to the feedback effects both policies may not be determined independently. It is also shown that depending on the region's size different types of the public input maximize growth.
Keywords: O41; H40; H54; R13; 330; Fiscal and institutional policy; regional growth; adjustment costs; congested public inputs